A Retrospective Study of Association of Tumor Budding, Tumor Microenvironment, and Clinicopathological Characteristics of Invasive Breast Carcinoma - Singh, Tanwi; Chandra, Kalpana; Kumar, Nidhish; Mishra, Anuja; Singh, Sanjeet; Singh, Anju; Kumar, Umesh; Kumar, Praveen (Journal of Laboratory Physicians, 2022)
Background Tumor budding (TB) has been identified in many solid cancers and thought to be involved in invasion and is the initial step in the metastatic process. Limited information is available documenting the role of tumor budding in breast carcinoma. With this aim, the present study evaluates the association of tumor budding, tumor microenvironment, and its correlation with clinicopathologic parameters.Materials and Methods A total of 102 cases were archived and evaluated for peripheral and intra tumoral budding along with tumor microenvironment on hematoxylin and eosin (H&E) slides.Statistical Analysis Correlation between tumor budding, tumor microenvironment, and other classical clinicopathological parameters was studied by Chi-square test. A p-value less than 0.05 was considered significant.Results Females constituted 99 cases out of 102 and 3 were males. We found 55.9% and 44.1% of patients in the age group less than or equal to 50 and greater than 50, respectively. Also, 65.6% of cases presented with small tumor size less than or equal to 5 cm, 80.39% with lymph node metastasis, and 76.4% with lympho-vascular emboli. High peripheral tumoral budding (PTB) was seen in 45.10%, low peripheral tumoral budding in 54.9%, high ITB in 53.9%, and low ITB in 46.1%. Necrosis was found only in 39.21%. Significant statistical association of PTB was found with lymph node metastasis, lymphovascular emboli, and tumor necrosis, whereas ITB with tumor grade, lymph node metastasis, lympho-vascular emboli, and necrosis. Both PTB and ITB showed no statistically significant correlation with age and size of the tumor.Conclusion Tumor budding is an independent adverse prognostic factor in invasive breast carcinoma. However, further work is needed to establish a standard method for the quantification of this parameter, which will help in effective stratification of patients in terms of disease-free survival and likely outcome.
Keywords: intratumoral budding; invasive breast carcinoma; peripheral tumor budding; prognosis; tumor budding